2011
DOI: 10.1016/j.jsps.2011.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Galactomannan gum coated mucoadhesive microspheres of glipizide for treatment of type 2 diabetes mellitus: In vitro and in vivo evaluation

Abstract: Type 2 diabetes mellitus is a heterogeneous disease of polygenic origin and involves both defective insulin secretion and peripheral insulin resistance. Studies have shown that post-meal hyperglycemic spikes are associated with increased cardiovascular mortality in type 2 diabetes. Over the past decade, a major interest in control of postprandial glucose excursion has emerged and a plethora of new medications that specifically target postprandial hyperglycemia were discovered. Despite the availability of new a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The height (h) of the heap formed was measured and the radius (r) of the cone base was also determined. The angle of repose ( ϕ ) was calculated as:20…”
Section: Methodsmentioning
confidence: 99%
“…The height (h) of the heap formed was measured and the radius (r) of the cone base was also determined. The angle of repose ( ϕ ) was calculated as:20…”
Section: Methodsmentioning
confidence: 99%
“…This may be the reason behind the distorted shape and rough surface of Sodium CMC microspheres [24]. At high concentration of the polymers (F2, F4, F8), some of the microspheres were fused to each other, which may be due to the presence of higher amount of water, which slowly evaporates upon stirring, causing the particles to come in contact with each other [25]. …”
Section: Resultsmentioning
confidence: 99%
“…In 2009, Hosmani et al (2) optimized SR microspheres of glipizide by using the factorial design method and reported the effect of the combinations of polymers (polycarbophil and sodium alginate) on drug entrapment (75%), yield (97%) swelling index (2.2), and mucoadhesion (100%), and the release of the drug was extended up to a period of 8 h. It showed a hypoglycemic effect by the oral glucose tolerance test (OGTT) test for a period of 1-9 h. Behera et al (42) prepared microspheres of glipizide with polymethacrylate and observed dissolution of the drug in alkaline pH and reported that the release of the drug was extended up to 8 h. There are some reports on the prolonged release of GLP from microspheres up to 24 h (33,43,44) in which the method of preparation of the products was quite time consuming and expensive in comparison with that of the present investigation.…”
Section: Study Of Drug Releasementioning
confidence: 99%